Factors of work stress among employees at TNB Kuala Pilah / Nor Fazerah Amir and Nurul Nabila Ain Ibrahim - Amir, Nor Fazerah; Ibrahim, Nurul Nabila Ain (Faculty of Business and Management, 2016)
Work stress is common issues in today’s organizations either for small organizations or large organizations and it has been recognized as a challenge for the employees and for the organization. Employees who faced the problems of work stress will either give positive effects or negative effects depend on how the employees receive and adapt to the situation. In this research, the aim is to conduct a research on the factors that create work stress among employees at TNB station Kuala Pilah. There are three independent variables that are the factors of work stress which are; workload, role conflict and interpersonal relationship at the workplace. This research was conducted at TNB station Kuala Pilah. 80 questionnaires were distributed to the employees randomly but only 76 questionnaires were received by the researchers. This research was conducted to answer the research questions and also the research objectives. The data collected were analysed by the researchers. The findings of this study indicate that workload is the most significant or influential factor that contributes to work stress in the organization. The study would be beneficial to the employees and company as they are facing stress at work. In the end of this research paper, the researchers discussed some recommendations as the best method for employees and employers at TNB Kuala Pilah to minimize their level of work stress and also for the future researchers.